Renal Vein Thrombosis secondary to pyelonephritis: Case presentation - Ganeshan, Anusha Skandini; Chongo, Angel Alberto Calderon (Open Science Journal, 2017)
The Renal Vein Thrombosis (RVT) is a rare pathology in adults as compared to children. It is usually present as a complication of other conditions as sepsis, hypercoagulable state, and malignancy. We present a male of age of 36 years, who suffered from RVT following pyelonephritis. Following all investigations, including blood tests, Computed Tomography (CT) of abdomen and CT angiogram, the concluding diagnosis of left RVT was made. Subsequent to confirmation of diagnosis, he was commenced an anticoagulation therapy with the low-molecular-weight heparin and warfarin. Consequently, the patient was discharged home with regular follow-ups on an outpatient basis with PT/INR checks. After 3 months, a control CT renal angiogram was performed, which revealed complete resolution of the Left RVT. In conclusion of this patient case, it can be stated that RVT is a rare condition which can have a good outcome with early diagnosis and subsequent appropriate anticoagulant therapy. In a view of this case, the review of the topic was made.